#TITLE_ALTERNATIVE# - OKTOKILIAN CHON (NIM : 22208324), REZA
Gundih Block comprises of naturally fractured wet gas reservoirs. It is located near Cepu City, Central Java, Indonesia. This block consists of three structures of KTB, RBT and KDL. These three structures with different depths of Gas Water Contact (GWC) have been predicted to have a high water production. On the other hand, the water-treating facilities at the surface are limited. To handle the predicted water produced from those three structures, a simulation study of water re-injection into aquifer body of RBT structure had been conducted in 2007. The 2007 reservoir simulation model (Model A) used combination of analytical (Carter Tracy) method and numerical (grid-blocks) method as the aquifer definition. Several sensitivity studies were performed to analyze the capability of Model A. The parameters of the sensitivity include aquifer size, injector perforation depth interval, permeability matrix, permeability fracture and constant injection rate. Further, a model that uses only grid blocks to define the aquifer and injection support (Model B) was applied. Model B uses a definition of aquifer-toreservoir height ratio (ha/he) to represent the aquifer strength. A sensitivity study for Model B was performed also based on the unique results of Model A sensitivity characteristics. Comparison between two sensitivity results of both models had been used as a tool to select the proper model that can be used to predict the influence of aquifer existence. The results of this study show that Model B is capable and more properly simulate the process than Model A are. This is because Model A gives uncommon or not clear results in cases of upper injector perforation interval, higher vertical fracture permeability and constant injection rate in several aquifer sizes. On the other hand, Model B may properly represent the influence of water injection into the aquifer for those sensitivity cases. In conclusion, Model B is more proper than Model A, and the proposed model for water injection study in RBT structure is Model B with ha/he value of 100.